Penerapan Video Media Interaktif untuk Meningkatkan Motivasi dan Hasil Belajar Shield Metal Arc Welding - Randa Avito Yasri; Ambiyar Ambiyar; Mulianti Mulianti (Jurnal Pendidikan Teknologi Kejuruan, 2019)
This research explores the application of video as an interactive media, learning motivation of students and student learning outcomes. The purpose of this research for motivation and student learning outcomes. This type of research this is a class action Research (PTK), the population and the sample used at the class XI welding techniques as much as 29 students. The instruments used in the form of interactive media, video observation sheets and test of mastery. Data obtained from the motivation of learning i.e. the percentage and the results of the study are average. The learning motivation of students in cycle I meetings I was 50.86% criteria less motivated; the Icycle meeting II was 64.22% criteria sufficiently motivated; and in cycle II meeting was 73.71% criteria I motivated; cycle II II meeting was 84.48% criteria are very motivated. The results of a study on cycle I with an average of 70.24 and cycle II with an average of 84.37. The use of video as an interactive media can increase motivation and learning results Subjects Shield Metal Arc Welding (SMAW) Welding Technique Class XI in SMK Negeri 1 Bukittinggi